Indian boarding home settlement approved by federal court - Needham, Fraser (APTN News, 2024)
The Indian boarding home class action settlement was officially approved by a Federal Court justice.
Canada

Ile-a-la Crosse school settlement stalled by Saskatchewan says Ottawa - Needham, Fraser (APTN News, 2023)
A settlement for students who went the to Ile-a-la Crosse residential school is stalled because Saskatchewan refuses to negotiate says Ottawa.
Canada
Keywords: 2023-06 June